Effects of external surface charges on the enhanced piezoelectric potential of ZnO and AlN nanowires and nanotubes - Seong Min Kim; Hyeok Kim; Youngmin Nam; Sungjin Kim (AIP Advances, 2012)
We theoretically investigate external surface charge effects on piezoelectric potential of ZnO and AlN nanowires (NWs) and nanotubes (NTs) under uniform compression. The free carrier depletion caused by negative surface charges via surface functionalization on vertically compressed ZnO and AlN NWs/NTs is simulated using finite element calculation; this indicates the enhancement of piezoelectric potential is due to the free carriers (electrons) being fully depleted at the critical surface charge density. Numerical simulations reveal that full coverage of surface charges surrounding the NTs increases the piezoelectric output potential exponentially within a relatively smaller range of charge density compared to the case of NWs for a typical donor concentration (∼1017 cm−3). The model can be used to design functional high-power semiconducting piezoelectric nanogenerators.